Exploring the Implication of Service Quality and Satisfaction on Behavioral Intentions in the Indian Aviation Industry - Das, Uday Sankar; Kumar Shome, Mihir (Journal of Neonatal Surgery, 2025)
National Civil Aviation Policy in 2016 has propelled significant growth in the Indian civil aviation industry, driven by increasing passenger traffic. The study explores the impact of service quality on customer satisfaction and purchase intention, along with the mediating role of customer satisfaction in the Indian cultural context. Data from 783 passengers across 13 airports and 9 airlines was collected using a modified SERVPERF questionnaire, incorporating American Customer Satisfaction Index and the Theory of Planned Behavior dimensions. Exploratory factor analysis identified underlying constructs, which were further examined to validate hypothesized relationships. The results demonstrate that service quality significantly affects customer satisfaction and purchase intention, with customer satisfaction acting as a partial mediator. This study also analyzes growth trends using DGCA Civil Aviation Statistics (2016–2023), highlighting significant passenger growth. The findings validate all hypotheses, offering strategic insights to enhance service quality and customer loyalty in the Indian aviation industry.